2011
DOI: 10.1111/j.1600-065x.2011.01040.x
|View full text |Cite
|
Sign up to set email alerts
|

Innate and adaptive immune responses to cell death

Abstract: Summary The immune system plays an essential role in protecting the host against infections and to accomplish this task has evolved mechanisms to recognize microbes and destroy them. In addition, it monitors the health of cells and responds to ones that have been injured and die, even if this occurs under sterile conditions. This process is initiated when dying cells expose intracellular molecules that can be recognized by cells of the innate immune system. As a consequence of this recognition, dendritic cells… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
170
1
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 200 publications
(173 citation statements)
references
References 136 publications
(238 reference statements)
0
170
1
2
Order By: Relevance
“…Local sterile inflammation after tissue injury and necrotic cell death has an important role in tissue repair (Rock et al, 2011), whereas systemic sterile inflammation or the cytokine storm triggered after major trauma can be lethal (Schneider et al, 2011). Recently, it has been reported that psychological and/or acute intense stressor exposure in the absence of overt tissue damage can evoke a detectable local and systemic sterile inflammatory response and that DAMPs may have a (Fleshner, 2013;Frank et al, 2015b;Maslanik et al, 2013;Miller et al, 2015).…”
Section: Stress Damps and Sterile Inflammationmentioning
confidence: 99%
“…Local sterile inflammation after tissue injury and necrotic cell death has an important role in tissue repair (Rock et al, 2011), whereas systemic sterile inflammation or the cytokine storm triggered after major trauma can be lethal (Schneider et al, 2011). Recently, it has been reported that psychological and/or acute intense stressor exposure in the absence of overt tissue damage can evoke a detectable local and systemic sterile inflammatory response and that DAMPs may have a (Fleshner, 2013;Frank et al, 2015b;Maslanik et al, 2013;Miller et al, 2015).…”
Section: Stress Damps and Sterile Inflammationmentioning
confidence: 99%
“…Cell death mechanisms that occur after irradiation include mitotic catastrophe, necrosis, apoptosis, autophagy, and senescence (Golden et al 2012). The response of immune cells to these cell death pathways leads to the production of cytokines that stimulate various signaling pathways in normal tissues (Rock et al 2011;Muralidharan and Mandrekar 2013). Immunogenic cell death pathways include necrosis and necroptotic.…”
Section: Immunogenicity Of Ionizing Radiationmentioning
confidence: 99%
“…Effects of radiation exposure are mediated by radiation-induced damage to DNA, organelles, and membranes. Intense damages after exposure to radiation stimulate immune responses that result in subsequent consequences (Rock et al 2011;Muralidharan and Mandrekar 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, apoptosis is considered to be immunologically ignored or functions to suppress immune activation via the induction of tolerance, with apoptotic bodies rapidly cleared by phagocytes. 1 In contrast, necrotic cell death is associated with loss of plasma membrane integrity, facilitating release of danger signals 2 or damage-associated molecular patterns 3 (DAMPs) including uric acid, 4 heat shock proteins (HSPs) 5 and mitochondrial constituents 6 that serve as endogenous immune adjuvants. DAMPs released from dying cells can stimulate an effective immune response against cellular antigen, in much the same way as pathogenic signals arising from infection.…”
mentioning
confidence: 99%